A non-catalytic vapor growth regime for organohalide perovskite nanowires using anodic aluminum oxide templates. Issue 18 (24th April 2017) - Tavakoli, Mohammad Mahdi; Waleed, Aashir; Gu, Leilei; Zhang, Daquan; Tavakoli, Rouhollah; Lei, Bingbing; Su, Wenjun; Fang, Fang; Fan, Zhiyong
Abstract : In this work, a novel and facile synthesis process to fabricate single crystalline organometal halide perovskite nanowires has been successfully developed. Abstract : In this work, a novel and facile synthesis process to fabricate single crystalline organometal halide perovskite nanowires has been successfully developed. Nanowires were grown in a high density ordered array from metal nanoclusters inside anodic aluminum oxide templates using a non-catalytic chemical vapor deposition method. Specifically, perovskite NWs were grown as a result of the reaction between methylammonium iodide (MAI) and the Pb/Sn (Pb or Sn) metal in anodic aluminum oxide templates under optimal conditions. The characterization results show that there is a reaction zone at the interface between the perovskite material and metal, at the bottom of the anodic aluminum oxide nanochannels. In order to sustain perovskite NW growth, MAI molecules have to diffuse downward through the perovskite NWs to reach the reaction zone. In fact, the reaction is facilitated by the formation of an intermediate product of the metal iodide compound. This suggests that the Pb/Sn metal is converted to PbI2 /SnI2 first and then perovskite NWs are formed as a result of the reaction between MAI and PbI2 /SnI2 through a vapor–solid–solid process. The optical characterization results demonstrate that the as-synthesized NWs with an ultra-high nanostructure density can serve as ideal candidates for optoelectronic devices, such as solar cells, light-emitting didoes, photodetectors, etc . And the reported growth approach here is highly versatile combining the merits of excellent controllability, cost-effectiveness and tunability on material composition and physical properties.